2006
DOI: 10.1186/cc4837
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Nosocomial pneumonia is a significant cause of inhospital morbidity and mortality. Oral care interventions have great potential to reduce the occurrence of nosocomial pneumonia. Studies using topical antiseptic agents yielded mixed results. We hypothesized that the use of chlorhexidine for oral decontamination would reduce the incidence of nosocomial pneumonia in patients requiring mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(20 citation statements)
references
References 28 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Center for Disease Control and Prevention (CDC) recommended a comprehensive oral hygiene program for mechanically ventilated patient [ 9 ]. A meta- analysis by Pineda and colleagues showed reduction in VAP among adult patients treated by decontamination with oral chlorhexidine [ 30 ]. Similar protective results were concluded by meta-analysis by Chlebichi and Safdar in which chlorhexidine rinse was used [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Center for Disease Control and Prevention (CDC) recommended a comprehensive oral hygiene program for mechanically ventilated patient [ 9 ]. A meta- analysis by Pineda and colleagues showed reduction in VAP among adult patients treated by decontamination with oral chlorhexidine [ 30 ]. Similar protective results were concluded by meta-analysis by Chlebichi and Safdar in which chlorhexidine rinse was used [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports vary on the potential impact of chlorhexidine use in other patient populations. When tested in intensive care populations outside cardiac surgery, chlorhexidine did not achieve the same positive outcomes in in regard to mortality and decreased length of stay (129,130), although evidence around possible decreases in VAP rates among severely ill patients intubated for more than 1 day is growing (131,132). Finally Klompas et al published an article on the reappraisal of routine oral care with CHG (133).…”
Section: Oral Carementioning
confidence: 99%
“…Importantly, however, cardiac surgery patients are generally extubated within 48 hours and thus have a low risk for VAP. However, in a recent meta-analysis, Pineda et al 22 found that chlorhexidine did not reduce nosocomial pneumonia or mortality rate. A recommendation for use of chlorhexidine in patients other than those having elective cardiac surgery is not included in national ventilator bundles or in recommendations from the Centers for Disease Control and Prevention because no evidence of the effectiveness of chlorhexidine in general critical care patients is available.…”
mentioning
confidence: 95%